Quality of Life among Patients with Acute Coronary Syndromes Receiving Care from Public and Private Health Care Systems in Brazil - de Carvalho Costa, Ingrid Maria Novais Barros; da Silva, Danielle Góes; Oliveira, Joselina Luzia Meneses; Silva, José Rodrigo Santos; de Andrade, Fabrício Anjos; de Góes Jorge, Juliana; de Oliveira, Larissa Marina Santana Mendonça; de Almeida, Rebeca Rocha; Oliveira, Victor Batista; Martins, Larissa Santos; Costa, Jamille Oliveira; de Souza, Márcia Ferreira Cândido; et al. (Clinics and practice, 2022)
(1) Background: Quality of life (QOL) is used as a health indicator to assess the effectiveness and impact of therapies in certain groups of patients. This study aimed to analyze the QOL of patients with acute coronary syndrome (ACS) who received medical treatment by a public or private health care system. (2) Methods: This observational, prospective, longitudinal study was carried out in four referral hospitals providing cardiology services in Sergipe, Brazil. QoL was evaluated using the Medical Outcomes Study 36-Item Short-Form Health Survey. The volunteers were divided into two groups (public or private health care group) according to the type of health care provided. Multiple linear regression models were used to evaluate QoL at 180 days after ACS. (3) Results: A total of 581 patients were eligible, including 44.1% and 55.9% for public and private health care, respectively. At 180 days after ACS, the public health care group had lower QoL scores for all domains (functional capacity, physical aspects, pain, general health status, vitality, social condition, emotional profile, and health) (p < 0.05) than the private group. The highest QoL level was associated with male sex (p < 0.05) and adherence to physical activity (p ≤ 0.003) for all assessed domains. (4) Conclusions: This shows that social factors and health status disparities influence QoL after ACS in Sergipe.